Visual Rhetoric in the English Renaissance Portrait. Contexts and Interpretations - Troitskaya, Anna A. (Actual Problems of Theory and History of Art, 2021)
Numerous studies on the English Renaissance have been devoted to the uniqueness and peculiarity of the English portraiture. Such means of visual representation as gesture, pose, costume, as well as ways to enhance the personality of a model through the adding of emblems and inscriptions became widespread during this period. All these elements can be considered as pictorial rhetorical formulas with fixed meanings. Among them, there are complex allegorical solutions, “talking” gestures, or allegorical background. Moreover, these and other examples appear simultaneously with the growing interest to individual interpretations of the portrait image, which indicates a certain stage in development of the English portrait. There is an approach based on the visual rhetorics concept among contemporary methods of art studies. It proposes that images can be analyzed as rhetorical structures. The paper offers a brief historiographic overview of the appearance of this approach and its application to English Renaissance painting. The aim of this study has been to define the visual rhetorics as an art-historical concept, and to demonstrate how the analysis of visual rhetorics tools became the key to the understanding of the 16th-century English art. The concept of visual rhetorics outlines the differences and similarities in the approaches to the English Renaissance art research. At the same time, it analyzes various artistic portraiture techniques of this time emphasizing the originality of the composition.